It's Time to Talk: Challenges in Providing Integrated Palliative Care in Advanced Congestive Heart Failure. A Narrative Review - Chow, Justin; Senderovich, Helen (Current Cardiology Reviews, 2018)
Background: Congestive heart failure is an increasingly prevalent terminal illness in a globally aging population. Prognosis for this disease remains poor despite optimal therapy. Evidence suggests that a palliative care approach may be beneficial – and is currently recommended – in advanced congestive heart failure but these services remain underutilized. Objectives: To identify the main challenges to the access and delivery of palliative care in patients with advanced congestive heart failure, and to summarize recommendations for clinical practice based on the available literature. Methods: MEDLINE and EMBASE were searched for articles published from 1995-2017 pertaining to end of life care in individuals suffering from CHF. Only four randomized controlled trials were found. Results: We identified ten key challenges to access and delivery of palliative care services in this patient population: (1) Prognostic uncertainty, (2) Provider education/training, (3) Ambiguity surrounding coordination of care, (4) Timing of palliative care referral, (5) Inadequate community supports, (6) Difficulty communicating uncertainty, (7) Fear of taking away hope, (8) Insufficient advance care planning, (9) Inadequate understanding of illness, and (10) Discrepant patient/family care goals. Provider and patient education, early discussion about prognosis, and a multidisciplinary team-based approach are recommended as we move towards a model where symptom palliation exists concurrently with active disease-modifying therapies. Conclusion: Despite evidence that palliative care may improve symptom control and quality of life in patients with advanced congestive heart failure, a multitude of current challenges hinder access to these services. Education, early discussion of prognosis and advance care planning, and multidisciplinary team-based care may be a helpful initial approach as further targeted work addresses these challenges.
Keywords: end-of-life